Effect of water stress on monoterpene emissions from young potted holm oak (Quercus ilex L.) trees (Oecologia, 1996)
We investigated the effects of a short period of water stress on monoterpene emissions from Quercus il- ex, a common oak species of the Mediterranean vegeta- tion and a strong emitter of monoterpenes. The experi- ment was carried out on two young saplings with a branch enclosure system under semi-controlled condi- tions. Under unstressed conditions, small qualitative (cis- [3-ocimene, trans-~3-ocimene, [3-caryophyllene and 1,8- cineol) and large quantitative (as much as 40% for the main compounds emitted) differences were observed be- tween the two apparently similar trees. Nevertheless these differences did not affect the short- and long-term responses to temperature and water stress. Daily courses of emissions and gas exchanges were similar before and after the stress. During the most severe stress, emissions were reduced by a factor of two orders of magnitude and the log-linear relationship between emissions and tem- perature no longer existed. Photosynthesis and transpira- tion rates decreased as soon as the soil started to dry, whereas monoterpene emissions slightly increased for few days and then dropped when the daily CO 2 balance approached zero. We concluded that under water stress monoterpene emissions were highly limited by monoter- pene synthesis resulting from a lack of carbon substrate and/or ATR After rewatering, both emissions and gas ex- changes recovered immediately, but to a level lower than the pre-stress level. These results have many implica- tions for monoterpene emission modelling in the Medi- terranean area, since the dry period generally extends from May to August. If our results are confirmed by field experiments, water stress could lead to a large overesti- mation of the emissions under summer conditions, when the algorithms based on light and temperature would give high emission rates.